2016
DOI: 10.1111/bju.13684
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome of the adjustable transobturator male system (ATOMS): results of a European multicentre study

Abstract: The ATOMS device is safe and shows high treatment efficacy and patient satisfaction in the largest cohort study to date. The latest generation, with its pre-attached silicone-covered scrotal port, is superior to its predecessors. Significantly better results were achieved with primary implantation and in those without a history of radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 30 publications
12
56
0
Order By: Relevance
“…Later, Friedl et al [33] analyzed the risk factor for ATOMS failure and concluded that previous ineffective implants are a significant factor for new implant removal. The long-term outcomes of the same ATOMS series confirmed secondary and tertiary implantation, also including failed ATOMS, are at higher risk of failure; while former urethral surgeries and strictures do not influence device durability [30]. However, titanium intolerance was the most frequent complication leading to explant in this series, associated to IP, an outdated design of device not used in our series.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Later, Friedl et al [33] analyzed the risk factor for ATOMS failure and concluded that previous ineffective implants are a significant factor for new implant removal. The long-term outcomes of the same ATOMS series confirmed secondary and tertiary implantation, also including failed ATOMS, are at higher risk of failure; while former urethral surgeries and strictures do not influence device durability [30]. However, titanium intolerance was the most frequent complication leading to explant in this series, associated to IP, an outdated design of device not used in our series.…”
Section: Discussionsupporting
confidence: 66%
“…The complications reported in studies with old-generation devices (mainly inguinal port [IP]) have little to do with studies that predominantly or exclusively report pre-attached scrotal port devices [14,30,31]. One study with the first-generation inguinal titanium port device described a high complication and explantation rate, but patient satisfaction was very high and 56% of the patients in this cohort would recommend the system to their best friends [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Irradiated patients should be cautioned about the greater risk of failure of the ProACT technique and increased risk of urethral erosion. Results of male slings in previously irradiated patients have also shown lower efficacy results although some adjustable slings have shown favorable results in this patient group . Impact of previous radiation on AUS safety and efficacy outcomes remains debated …”
Section: Discussionmentioning
confidence: 99%
“…14 have also shown lower efficacy results 28 although some adjustable slings have shown favorable results in this patient group. 35,36 Impact of previous radiation on AUS safety and efficacy outcomes remains debated. 37,38 Male slings are primarily indicated for mild and moderate patients, 26 while AUS is typically reserved for more severe patients.…”
Section: Discussionmentioning
confidence: 99%